Women's status: levels, determinants, consequences for malnutrition, interventions, and policy - Haddad, Lawrence James (1999)
This paper uses a gendered conceptual framework of the determinants of child survival, growth, and development to organize a review of the latest evidence on the strength of causal linkages between child nutrition outcomes and the relative status of women in seven Asian countries. Using a variety of indicators, the paper demonstrates the considerable variation in the status of women relative to men in the seven countries. Of the seven study countries, the status of women relative to men is lowest in Pakistan, India, and Bangladesh. The paper also reaffirms that equality in women's status relative to men's controlling for a host of socioeconomic factors, has a positive impact on child growth and discourages the intergenerational perpetuation of gender-based discrimination. The paper explores some of the economic and cultural explanations for the relatively poor status of women in the countries in question and draws out implications for policy and project design. Efforts to modify policy and project design to counter gender discrimination will rely on the effective monitoring of the status of women and the supportiveness of the enabling legal environment.